People Analytics To Mitigate Managerial Decision Bias In Modern Organizations - Setyawan, Rachmad; Faradila, Silvia (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
The increasing complexity of contemporary organizations creates greater possibilities for cognitive bias to affect executive decision processes. The People Analytics method provides organizations with a data-based solution that improves their ability to make unbiased decisions. The research study investigates how People Analytics technology helps reduce inaccuracies in managerial decision-making. The research uses a quantitative explanatory method to investigate middle and upper management personnel who use human resource information, using a survey. The researchers employed linear regression analysis to examine their data. The results of the study show that People Analytics usage leads to a significant reduction in executive decision-making biases, helping organizations make more unbiased and consistent decisions. The research study establishes its value through the combination of People Analytics and decision bias theory within a universal management framework. The research findings demonstrate that People Analytics serves as a strategic tool that enhances both the quality and accountability of executive decisions.